Water stress and accelerated aging effects on the viability of osmoconditioned Chorisia speciosa seeds - Fanti, Silmara Cristina; Perez, Sonia Cristina Juliano Gualtieri de Andrade (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the efficiency of osmotic conditioning on the tolerance increase of seeds of Chorisia speciosa St. Hil. to water stress and accelerated aging. The seeds previously scarified (punction) were primed in KNO3 (0.1M) solutions at 20oC during 24 hours. After that, the seeds were dried (at 27oC) until the initial moisture level, presented before the pre-imbibition, was reached. Primed and non primed seeds were exposed to water stress simulated with PEG 6000 solutions, with 0.0, -0.1, -0.2, -0.3, -0.4, -0.5, -0.6 and -0.7 MPa of osmotic potentials and to accelerated aging at 45oC and 100% of RU during 0, 24, 48, 72, 96 and 120 hours. The mean values of rate and germination percentage were higher in primed seed than in non primed ones. The tolerance limit to water stress was extended for primed seed. Primed seeds were more sensible to accelerated aging.